2009
DOI: 10.1364/josaa.26.001375
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of early state of cyanopsia with subjective color settings immediately after cataract removal surgery

Abstract: We evaluated cyanopsia by means of achromatic-point settings at several time points started from the day before intraocular lens (IOL) implantation for cataract removal surgery. We intensively measured the initial drift in color appearance; we started the measurement less than 30 min after eyepatch removal, and the measurement continued for several weeks. The shifts were mainly observed in the direction of color space that selectively varies short-wavelength-sensitive cone (S-cone) responses. The time constant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
11
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 44 publications
2
11
0
Order By: Relevance
“…This visual phenomenon has been reported in the initial period after cataract surgery, 18,22,24,25 with a tendency to resolve by 3 months postoperatively. 18,24 In a study of eyes having cataract surgery with the implantation of a clear or yellow IOL by Hayashi and Hayashi,18 no patient reported cyanopsia 3 months after surgery, suggesting that some form of neural adaptation or color constancy occurred. Kitakawa et al 24 evaluated cyanopsia using achromatic-point settings at several timepoints starting from the day before clear IOL implantation during cataract surgery.…”
Section: Discussionsupporting
confidence: 60%
See 2 more Smart Citations
“…This visual phenomenon has been reported in the initial period after cataract surgery, 18,22,24,25 with a tendency to resolve by 3 months postoperatively. 18,24 In a study of eyes having cataract surgery with the implantation of a clear or yellow IOL by Hayashi and Hayashi,18 no patient reported cyanopsia 3 months after surgery, suggesting that some form of neural adaptation or color constancy occurred. Kitakawa et al 24 evaluated cyanopsia using achromatic-point settings at several timepoints starting from the day before clear IOL implantation during cataract surgery.…”
Section: Discussionsupporting
confidence: 60%
“…18,24 In a study of eyes having cataract surgery with the implantation of a clear or yellow IOL by Hayashi and Hayashi,18 no patient reported cyanopsia 3 months after surgery, suggesting that some form of neural adaptation or color constancy occurred. Kitakawa et al 24 evaluated cyanopsia using achromatic-point settings at several timepoints starting from the day before clear IOL implantation during cataract surgery. They found that color appearance was recalibrated during cyanopsia by neural mechanisms with a time constant of several hours.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This suggests that even within the 2 days before testing there was some recalibration of perceived focus, again because the subjective focus settings changed less than would be expected from the optical changes. A rapid initial adjustment has also been reported for color appearance changes after cataract surgery (Delahunt et al, 2004; Kitakawa et al, 2009). …”
Section: Discussionmentioning
confidence: 84%
“…Following replacement of the lens with an intraocular lens (IOL), achromatic settings took months to return to near their pre-surgery settings. These slow drifts are distinct from the short-term normalization that also occurs when subjects are exposed to an adapting field, or when cataract patients are adapted to an external stimulus [24]. Delahunt et al isolated the long-term component by measuring the white settings while observers were dark-adapted, thus removing the adaptation to the immediate “extrinsic” light environment in order to reveal the underlying “intrinsic” white balance of the observer.…”
Section: Introductionmentioning
confidence: 99%